Refractory Hypotension as an Initial Presentation of Bilateral Subclavian Artery Stenosis - Maxwell Eyram Afari; John V. Wylie; Joseph P. Carrozza (Case Reports in Cardiology)
Bilateral subclavian stenosis is a rare clinical condition. An interbrachial pressure difference of 15 mm Hg can raise suspicion for unilateral subclavian artery stenosis, but the diagnosis of bilateral subclavian artery stenosis can be challenging. We present a case of a 75-year-old woman who presented with refractory hypotension after surgery. Initial vitals revealed blood pressure in the 60s/50s mm Hg in both arms. Cardiopulmonary examination was remarkable for diminished pulses in all 4 extremities and audible carotid bruits. She continued to be hypotensive despite aggressive fluid resuscitation. Troponin T peaked at 0.24 ng/mL (reference < 0.04), and an echocardiogram revealed a reduction in ejection fraction (37% from 50%). Left and right heart catheterization demonstrated normal filling pressures and cardiac output. During the procedure, however, it was noted that the patient’s central blood pressure was 70–80 mm Hg higher than cuff pressures obtained in either arm. Selective angiography revealed 90% left subclavian ostial stenosis as well as 70% stenosis of the right subclavian artery.